The development in the understanding of the concept of death among black South African learners from the Eastern Cape, South Africa - Tembeka N Mdleleni-Bookholane; Willie J Schoeman; Ilze van der Merwe (AOSIS, 2004)
Thirty-one learners aged 6-16 were selected using purposive sampling, with the aim of investigating their understanding of death. Opsomming Een-en-dertig leerders tussen 6 en 16 jaar is geselekteer met die doel om hulle begrip van dood te ondersoek. *Please note: This is a reduced version of the abstract. Please refer to PDF for full text.